La critique d’espace public : dire le politique du projet de paysage - Collectif Critique et projet de paysage (Projets de Paysage)
Since 2018, a group of practitioners and researchers from schools of architecture and/or landscape architecture noting the scarcity of criticism of the landscape architecture of public spaces, and particularly of the landscape projects at the inception of these spaces, has been seeking to define the epistemological conditions for such a critique and has thus investigated the political dimension of the designing of the public space. The article presents four critiques carried out by the group between 2018 and 2020 of landscape projects: the Linear Forest (Paris), the Coeur de Maine (Angers), the Place des Artisans (Lille) and the Place Jean-Jaurès (Marseille). Based on these critiques, the article identifies two guidelines to assess the potentiality of landscape projects in assuming their political objective in the creation of the public space: the dialectic of the programme and the place, and the dialectic of its extension and the uses made of it.